Faktor Determinan Disfungsi Seksual pada Pasien Kanker Serviks - Lasut, Margareth; Nuraini, Tuti; Gayatri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study Aims to identify any factors that determine the incidence of sexual dysfunction in cervical cancer patients. The method used in this article is a systematic review uses several databases such as Pubmed, Ebscohost, Proquest, Science Direct and Scopus. The article analysis process uses the PRISMA method. The result of this study showed that the incidence of sexual dysfunction in cervical cancer patients is generally not only caused by a decrease in the patient’s physical function, but is also influenced by the patient’s Bio, Psychological, social and spiritual factors. The Conclusion of this systematic review is that to overcome the various factors that cause dysfunction in cervical cancer patients. It is necessary for the cervical cancer patients to adapt with these factors. Moreover, to help cervical cancer patients overcoming the problem caused by sexual dysfunction, a good theraupeutical strategy is also needed to deal with the symptoms caused by the desease as well as the cancer’s therapy and treatment. Key words : Sexual Dysfunction, Factors Related to, Cervical Cancer Patient